2019
DOI: 10.1109/access.2018.2886245
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Robot Path Planning Based on Multi-Objective Particle Swarm Optimization

Abstract: In this paper, a new method is proposed for the path planning of multi-robots in unknown environments. The method is inspired by multi-objective particle swarm optimization (MOPSO) and is named multi-robot MOPSO. It considers shortness, safety, and smoothness. Due to the obscurity of the environment, the robots should decide the moving direction based on the information gathered by sensors only such that the optimal path between the start and goal positions can be found at the end of the algorithm. Sharing kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…On the other hand, some research provide methods, which are PSO-based algorithms in a network condition [101][102][103][104]. Some research has focused on solving the multi-robots CFPP problem while using PSO [105,106]. In Table 6, additional information from previous research related to PSO is shown.…”
Section: Refmentioning
confidence: 99%
“…On the other hand, some research provide methods, which are PSO-based algorithms in a network condition [101][102][103][104]. Some research has focused on solving the multi-robots CFPP problem while using PSO [105,106]. In Table 6, additional information from previous research related to PSO is shown.…”
Section: Refmentioning
confidence: 99%
“…In regard to multi-objective optimization in multi-robot systems, MOPSO [40] and multi-ACO [41] have already been applied to path planning problem. Broadly speaking, the metaheuristic algorithms are often applied in path planning problems compared to other issues, mainly, because optimization is the core study for finding a short and smooth path.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, a multi-objective evolutionary algorithm (MOEA) has been utilized in the proposed GA to approximate the Pareto optimal solution of any given environment settings for hTetro. Similar approaches that model multi-objective optimization problems (MOOP) for robot path planning tasks and attempt to solve them through evolutionary algorithms are shown in the works of [46] and [47].…”
Section: Introductionmentioning
confidence: 98%